(untitled) (The Review of Diabetic Studies, 2024)
Background Anesthesia practice relies on airway management, mechanical ventilation, and real-time monitoring to ensure patient safety during surgical procedures. Specialized equipment, including endotracheal tubes, supraglottic devices, ventilators, capnography, and pulse oximetry, has evolved from rudimentary inhalers to advanced workstations, addressing historical risks like hypoxia and barotrauma.​ Methods This narrative review synthesizes historical developments, design principles, clinical applications, and safety profiles of contemporary anesthesia equipment. Sources include peer-reviewed literature on airway devices, ventilation circuits, monitoring modalities, and emerging technologies like closed-loop systems.​ Results Key advancements include piston-driven ventilators with fresh gas decoupling for precise low tidal volumes, video laryngoscopes improving intubation success, and integrated monitors detecting disconnections via waveforms. Integration reduces human error, supports low-flow anesthesia, and enhances outcomes in high-risk cases, though challenges persist in resource-limited settings.​ Conclusions Modern anesthesia equipment transforms care into a technology-driven science, minimizing complications through precision and alarms. Future directions emphasize AI, sustainability, and portable systems to bridge global disparities and optimize safety.​